2013
DOI: 10.1016/j.autcon.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of modeling architectural detailing for predicting unreinforced masonry response to subsidence

Abstract: Publication informationAutomation in Construction, Publisher Elsevier Item record/more information http://hdl.handle.net/10197/4854 Publisher's statementThis is the author's version of a work that was accepted for publication in Automation in Construction. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Once the mesh is available, it can be used within several computational tools for the structural analysis of historic masonry buildings. Particularly, such approaches are usually based on: a) the finite element method (FEM) [29,30,31,32,33,28,34,35]; b) the discrete element method (DEM) [36,37]; and c) limit analysis [38,39]. Interesting comparisons of computational techniques are provided in [40,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Once the mesh is available, it can be used within several computational tools for the structural analysis of historic masonry buildings. Particularly, such approaches are usually based on: a) the finite element method (FEM) [29,30,31,32,33,28,34,35]; b) the discrete element method (DEM) [36,37]; and c) limit analysis [38,39]. Interesting comparisons of computational techniques are provided in [40,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…However, new numerical studies performed by Son and Cording [35] demonstrated that the structural response to excavation-induced ground movements is highly dependent on both cracking in the structure and structural type. This was confirmed by Truong-Hong and Laefer [38]. By employing a smeared crack model for masonry, they analyzed 16 FE models on masonry walls subjected to excavation-induced settlements, to investigate the impact on the building response of three particular window shapes, window size and brick orientation.…”
mentioning
confidence: 82%
“…Landolfo et al [15] employed similar homogenized FE model and predicted the failure modes of two-story masonry wall façades induced by differential settlement. Truong-Hong and Laefer [16] devised FE models and investigated the influence of window shape and size, block orientation, and lintels on the failure of masonry walls caused by excavation subsidence. Malena et al [17] combined the piecewise rigid displacement (PRD) method and the FE approach and studied the failure of masonry arch bridge caused by pier displacement.…”
Section: Introductionmentioning
confidence: 99%